Stiffness-dependent cellular internalization of matrix-bound BMP-2 and its relation to Smad and non-Smad signaling. (December 2016) - Gilde, Flora; Fourel, Laure; Guillot, Raphael; Pignot-Paintrand, Isabelle; Okada, Takaharu; Fitzpatrick, Vincent; Boudou, Thomas; Albiges-Rizo, Corinne; Picart, Catherine
Graphical abstract: Abstract: Surface coatings delivering BMP are a promising approach to render biomaterials osteoinductive. In contrast to soluble BMPs which can interact with their receptors at the dorsal side of the cell, BMPs presented as an insoluble cue physically bound to a biomimetic matrix, called here matrix-bound (bBMP-2), are presented to cells by their ventral side. To date, BMP-2 internalization and signaling studies in cell biology have always been performed by adding soluble (sBMP-2) to cells adhered on cell culture plates or glass slides, which will be considered here as a "reference" condition. However, whether and how matrix-bound BMP-2 can be internalized by cells and its relation to canonical (SMAD) and non-canonical signaling (ALP) remain open questions. In this study, we investigated the uptake and processing of BMP-2 by C2C12 myoblasts. This BMP-2 was presented either embedded in polyelectrolyte multilayer films (matrix-bound presentation) or as soluble form. Using fluorescently labeled BMP-2, we showed that the amount of matrix-bound BMP-2 internalized is dependent on the level of crosslinking of the polyelectrolyte films. Cav-1-mediated internalization is related to both SMAD and ALP signaling, while clathrin-mediated is only related to ALP signaling. BMP-2 internalization was independent of the presentation mode (sBMP-2 versus bBMP-2) for low crosslinked films (soft, EDC10) in striking contrast with high crosslinked (stiff, EDC70) films where internalization was much lower and slower for bBMP-2. As anticipated, internalization of sBMP-2 barely depended on the underlying matrix. Taken together, these results indicate that BMP-2 internalization can be tuned by the underlying matrix and activates downstream BMP-2 signaling, which is key for the effective formation of bone tissue. Statement of Significance: The presentation of growth factors from material surfaces currently presents significant challenges in academic research, clinics and industry. Being able to deliver efficiently these growth factors by a biomaterial will open new perspectives for regenerative medicine. However, to date, very little is known about how matrix-bound growth factors are delivered to cells, especially whether they are internalized and how they are signaling to drive key differentiation events. These initial steps are crucial as they will guide the subsequent processes leading to tissue regeneration. In this work, we investigate the uptake and processing by cells of BMP-2 ligands embedded in polyelectrolyte multilayer films in comparison to soluble BMP-2. We show that BMP-2 responsive cells can internalize matrix-bound BMP-2 and that internalization is dependent on the cross-linking level of the polyelectrolyte films. In addition, we show that internalization is mediated by both clathrin- and caveolin-dependent pathways. While inhibiting clathrin-dependent endocytosis affects only non-canonical signaling, blocking caveolin-1-dependent endocytosis reduces both canonical and non-canonical BMP signaling. The signaling pathways found for matrix-bound BMP-2 are similar to those found for soluble BMP-2. These results highlight that BMP-2 presented by a biomaterial at the ventral side of the cell can trigger major endocytic and associated signaling pathways leading to bone regeneration.